Sipakatau Culture and Character Education (Ethnographic Studies on the Bugis-Barang Soppeng Society of South Sulawesi) - Tang, Muhammad; Ismail, Ismail; Samsuduha, St; Markuna, Markuna (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The Sipakatau culture that grows and develops in the Bugis community in Barang. In addition, in an effort to preserve cultural values in society through education. This study is based on field research with qualitative-ethnographic methods which intends to describe Sipakatau cultural values as character education values. The results of this study indicate that all values in the Sipakatau culture that grow and develop in the Bugis community in Barang can be absorbed into character education values. The values in question are: 1) sipakalebbi' (appreciating and respecting), (2) sipakainge' (advising each other), (3) simasei (mutual love), (4) sinoreng (mutual help/helping), (5) sipatokkong (supporting each other) -protecting), (6) mapaciing (maintaining cleanliness), (7) assirumpungeng (togetherness and unity), (8) caring, and (9) respecting human rights. Then the pattern of inculcating these values in the Bugis community in Barang occurs in the three centers (tricenters) of education, namely; at the family level the pattern of inculcating character values begins with the introduction and understanding of good things to children, habituation, and parents being exemplary examples (uswah hasanah); at the school level the pattern of inculcating character values with habituation and educators (teachers) being role models; while at the community level the pattern of inculcating character values through informal institutions and community leaders becomes an example in the community. The character values and planting patterns contained in the Sipakatau culture can be internalized to students through the education tricenter (family, school, and community levels). This research has implications for the development of knowledge in the field of character education based on local wisdom.